2005
DOI: 10.1166/jnn.2005.012
|View full text |Cite
|
Sign up to set email alerts
|

Valve Morphogenesis in the Diatom Genus Pleurosigma W. Smith(Bacillariophyceae): Nature's Alternative Sandwich

Abstract: The loculate ("chambered") valve structure of centric diatoms like Triceratium favus Ehrenberg has been mentioned time and again in the nanostructure literature. Here we draw attention to the fundamentally different alternative sandwich model nature developed in the genus Pleurosigma, where it is nonloculate. This has so far been overlooked in nanostructural studies. We suggest some mechanical aspects that would offer interesting avenues for experimental testing. The first description of the natural fabricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…The apex of the specimen pictured by Reid (2002, fig. 24) in internal view is apparently eroded, with an atypical areola pattern that might be interpreted as an early stage of the valve morphogenesis (Sterrenburg et al 2005). Specimens analysed in the present study are not eroded and show apical details that could be considered consistent with those described by Reid (2002, fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The apex of the specimen pictured by Reid (2002, fig. 24) in internal view is apparently eroded, with an atypical areola pattern that might be interpreted as an early stage of the valve morphogenesis (Sterrenburg et al 2005). Specimens analysed in the present study are not eroded and show apical details that could be considered consistent with those described by Reid (2002, fig.…”
Section: Discussionsupporting
confidence: 74%
“…Specimens of the type material pictured by Reid (2002, figs 24, 26) show the areolar pores adjacent to the raphe-sternum crossed by bars whilst elsewhere they do not show bars. In Sterrenburg et al (2005), it was shown that such bars develop in the last stage of valve formation, but not necessarily in all pores.…”
Section: Pleurosigma Hinzianummentioning
confidence: 99%
“…At the margin, the two valve layers are fused, so that there is a monolayer structure. The entire process has been documented for Pleurosigma in Sterrenburg et al (2005). Exactly the same morphology is seen in H. nipkowii and will here be demonstrated in other new Haslea species, where the two valve layers are also shored by longitudinal rows of columns, the spaces in between being partially filled in, resulting in perforated longitudinal "bulkheads" we call saepes (Latin: "fence", plural: saepes) here.…”
Section: H Nipkowii (Meister) Poulin and Massé (Figs 1-9)supporting
confidence: 63%
“…These fissures can be interpreted as the result of fusion of the separate external slits present in Gyrosigma species. Because of the perforated saepes, the valve interior resembles the "parking-garage" aspect present in Pleurosigma (Sterrenburg et al 2005) and Gyrosigma.…”
Section: H Nipkowii (Meister) Poulin and Massé (Figs 1-9)mentioning
confidence: 99%
“…Over the past 10 years, information on the valve morphogenesis of diatoms has greatly increased (e.g. Cox, 1999;Tiffany, 2002Tiffany, , 2005Tiffany, , 2008Cox & Kennaway, 2004;Sterrenburg et al, 2005;Tiffany & Hernandez-Becerril, 2005;Kaluzhnaya & Likhoshway, 2007). However, although it has become clear that some aspects of valve morphogenesis have phylogenetic significance at higher taxonomic levels (Mann, 1984;Mayama & Kuriyama, 2002), there is still insufficient information to reveal how structure and ontogenetic patterns have evolved in the major diatom groups, especially among the lineages of bipolar centrics.…”
Section: Introductionmentioning
confidence: 99%